(untitled) (Heritage, 2020)
This study analyses the process of adopting of the sign language with deaf and hard of hearing preschool children in the context of the result of linguistic and psycholinguistic research. The importance of the sign language is emphasized and its historical development is analyzed. It is pointed to the significance of the critical period for the adoption and the learning of the sign and spoken language with deaf and hard of hearing preschool children. The sign language is natural and primary linguistic expression of deaf children. Deaf and hard of hearing children are exposed to the sign and spoken language, they have better understanding and linguistic production than the children who are only exposed to the spoken language. Bilingualism involves the knowledge and the regular use of the sign language, which is used by the deaf community, and of the spoken language, which is used by the hearing majority. Children at the preschool age should be enabled to continue to adopt the language they started to adopt within the family (the sign language or the spoken language). Children will adopt the best both linguistic modalities through the interaction with other fluent speakers (the adults and children).